2016
DOI: 10.1097/ijg.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Arterial Flow in Pseudoexfoliation Glaucoma and its Role in Diagnosing the Disease

Abstract: Flow dynamics of carotid arterial system exhibits different characteristics in individuals with XFG than controls. Such differences may serve as a basis for developing potentially new diagnostic biomarkers of XFG. Further studies are justified for examining the carotid flow in pseudoexfoliation syndrome and compare it against XFG for determining its power in differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…19 The same cut-off on the RI of CCA produced 90% sensitivity and 73% specificity. 7 Our study had limitations. It included small sample size and selection bias.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…19 The same cut-off on the RI of CCA produced 90% sensitivity and 73% specificity. 7 Our study had limitations. It included small sample size and selection bias.…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, peak systolic velocity (PSV, cm/s) and end‐diastolic velocity (EDV, cm/s) were measured at the intersection of OA with optic nerve (ie, 20–25 mm behind the eyeball in the nasal section of the orbit), and at 1 to 3 mm distance beyond the posterior pole of the eyeball, respectively. Then, resistivity index (RI) was calculated via RI = (PSV − EDV)/PSV for both OA and CRA 7 . Figures 1 and 2 depict example scans demonstrating the anatomical images of an eye and Doppler‐based measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, our results corroborate in part previous studies that have pointed out vascular alterations (accessed by different methods) and ET-1 elevation in patients with glaucoma, especially in those with normal tension glaucoma. 19,35 Regarding the main ndings of our study (ET1, LDI and NC results), we will separately address and contextualize each of our main ndings. Firstly, about ET-1, Grieshaber and Flammer had previously associated serum ET-1 levels with the pathogenesis of DH in these eyes with low-IOPs, within a more systemic context of primary vascular dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the patient-specific treatment schemes has gained importance in glaucoma management recently, the vascular parameters are gradually becoming important in terms of diagnosis, progression, and treatment algorithms especially in XFG, which is known to affect the vascular system more and cause increased vascular resistance. [18][19][20][21][22][23][24] Even a comprehensive slit-lamp examination is sufficient to diagnose XFS, and XFG is a clinical diagnosis depends on detection of glaucomatous damage; in particular cases with XFS it is hard to determine whether the VF defect is related with glaucoma or related with other co morbidities. Yarmohammadi et al 25 have found that that OCTA potentially shows promise for identifying focal glaucomatous damage before the first VF defect develops.…”
Section: Discussionmentioning
confidence: 99%